Strategies for Enhancing Public Services in the Era of Digitalization in Indonesia - Febby Aulya Putri; Lubna Salsabila; Timbul Dompak (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Public service reflects the state's role in fulfilling the needs of society in a fair and transparent manner. In the rapidly evolving digital era, public services in Indonesia have undergone significant transformation through the utilization of information technology. This study aims to examine strategies for improving the quality of public services in Indonesia in response to digitalization, emphasizing the importance of adapting to digital technologies to deliver more efficient, transparent, and accountable services. A qualitative descriptive approach was employed, analyzing various literature and regulations related to public services and digital transformation. The results indicate that digitalization has had a positive impact on the enhancement of public service quality, particularly in terms of accessibility, efficiency, and public participation. E-government and online service systems have proven effective in reducing bureaucracy, increasing public satisfaction, and strengthening the principles of good governance. However, challenges such as the digital divide and infrastructure readiness remain critical obstacles. Therefore, public service strategies in the digital era must involve active collaboration between the government and society, along with strengthening technological capacity and human resources. With this approach, digital transformation in public services can be more inclusive and sustainable.